Islamic Fintech Digital Transformation: Organizational Readiness and Data Protection Compliance in Indonesia's 2025 Regulatory Framework - Savandha, Septien Dwi; Safii, Nur Muhamad (Al-Makki Publisher, 2025)
The rapid growth of Islamic fintech in Indonesia coincides with the enactment of Law No. 27/2022 on Personal Data Protection (UU PDP), creating challenges for organizations to comply with both. This study reviews how organizations prepare for Sharia-compliant digital transformation under these laws. A systematic review of 73 studies from 2020-2025, following PRISMA, identified relevant peer-reviewed articles, conference papers, and regulations on readiness and Islamic fintech. Thematic analysis revealed seven key readiness dimensions: technological infrastructure (91.8%), Sharia compliance (87.7%), regulatory adaptation (80.8%), human capital (76.7%), financial resources (69.9%), organizational culture (64.4%), and stakeholder engagement (58.9%). UU PDP compliance issues, especially data protection officers (80.9%), significantly affect organizations. Success factors include leadership and Sharia board integration, though assessment frameworks lack empirical validation. Islamic fintech needs unique readiness considerations beyond traditional models, with religious governance as a new key dimension. However, reactive compliance and validation gaps highlight opportunities for improvement in organizational strategies.